Recaudación del impuesto predial y eficacia de los GAD ecuatorianos - Silverio Vásquez, Nery Mariuxi (2024)
The redistribution of resources, through policies and programs that seek to increase access to these services and resources, can significantly improve the quality of life of the most disadvantaged, reduce poverty and social exclusion, and contribute to a more just and inclusive society. In addition, resource redistribution can also improve stability and economic growth by increasing domestic demand, reducing inequality, and fostering investment and innovation. The research aimed to analyze the collection of property tax and the effectiveness of Ecuadorian decentralized autonomous governments, using a quantitative methodology that included analysis of statistical data and a questionnaire applied to a sample of 383 people. A correlational and statistical descriptive approach was used to approve the hypothesis that property tax collection improves the effectiveness of Ecuadorian decentralized autonomous governments. The research was nonexperimental and used analytical, statistical and synthetic methods, as well as inductive and deductive methods. The results indicate the approval of the null hypothesis proposed, and disparity in relation to the variables. The importance of improving tax culture and citizen participation in the decision-making process for the development of the country is highlighted.